Rancang Bangun Chatbot Berbasis Kecerdasan Buatan Terintegrasi Untuk Otomatisasi Layanan Pelanggan Melalui Platform Pesan Singkat Pada Bisnis Xyz - Irza Maulana Ramadhan; Dwi Fatrianto Suyatno (CV. SINAR HOWUHOWU, 2026)
Customer service through WhatsApp is widely used by small and medium-sized businesses. However, manual customer service often leads to slow response times, repetitive interactions, limited operating hours, and difficulties in managing customer data and transactions. This study aims to design and develop an artificial intelligence-based chatbot integrated with a web dashboard to automate customer service for Business XYZ. The system was developed using the Agile Development methodology consisting of planning, design, development, testing, deployment, and review stages. The implementation integrates WhatsApp, React.js, Node.js, Supabase, OpenAI, Biteship API, and QRIS Dynamic payment services into a centralized platform. The chatbot is capable of providing product information, processing orders, calculating shipping costs, handling payments, tracking order status, and performing automated customer follow-up. System functionality was evaluated using Black-Box Testing, and all major features operated according to the expected results. The developed system successfully improves customer service automation while providing an integrated platform for managing products, customers, and transactions.